Do enfrentamento e da vivência com o câncer: a avaliatividade no discurso do sofrimento - Nichele, Alessandra Medianeira Ilha (2014)
Through language we represent, under many ways, our emotional reactions. This way, verbalization of human experience takes the realization of meanings construction system. In this perspective, under Systemic Functional Grammar light (HALLIDAY; HASAN, 1989; HALLIDAY; MATTHIESSEN, 2004) and, specially, from The Appraisal System (MARTIN; WHITE, 2005), we have investigated which evaluative marks are recurrent in the discourse of people who experience cancer. In this sense, this research emphasis is on semantic valuation of suffering discourse, which is supported by Martin e White (2005) theoretical framework. The aim of this study is to chart which lexical choices and attitudinal resources build, by recurrence, the discourse of people who experience cancer. The corpus is composed by 10 interviews collected from Oncoguia portal, from the link Aprendendo com Você . In this context, the interviews take a great social relevance, in the humanistic sense, as a sharing of experiences, since they act breaking group, individual, social isolation; they can also serve to the pluralization of voices and to the democratic distribution of information (MEDINA 2008, p. 8), specially for being a huge fragility situation. The methodological procedures encompass the following stages: (1) elaboration of a list of words, through WordList resource (SCOTT, 2008); (2) identification and quantification of the most recurrent lexico-grammatical categories; (3) identification and categorization of the semantic subsystems of affect, judgment and appreciation; (4) semantic-interpretative data analysis. The results indicate a great recurrence of tenacity judgment categories and positive capacities, followed by affect for insecurity. Through judgment recurrences it is evident that overcoming is the watchword for the experiencers, who are determined to face and win cancer, since this is the only way of not submitting to mortality. The affect recurrences, focusing on the insecurity semantic field, indicate that the suffering experience triggers feelings of vulnerability and despair, bringing great sorrow for the fear of finiteness of life. The lexico-grammatical level investigations, more specifically in the ideational metafunction (HALLIDAY; MATTHIESSEN, 2004) indicate frequency of lexical marks in the first person, of relational processes (mainly to be ) and the intensifiers, which contributes for the painful experience manifestation the interviewees go through.